Bioavailability of alfalfa calcium - L.H. Harbers; G.M. Ward; A.D. Dayton (Kansas Agricultural Experiment Station Research Reports, 1984)
The availability of oxalate and non-oxalate calcium in alfalfa was determined using a chick assay. Oxalate-bound calcium was found to contribute only 16% as much influence as nonoxalate calcium. The nonoxalate calcium in alfalfa was 18% more available than calcium carbonate (precipitated chalk).; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Calcium; Alfalfa; Weight gain; Intake